SIMULATING OF FUTURE CLIMATE CONDITIONS ON THE EFFECT OF IRRIGATION ON SUGARCANE YIELD IN SOUTHERN BRAZIL - Mattos, Eduardo de Castro; TomÃ©, ThaÃs Cattarine Henriques; Menillo, Rafael Braghieri; Marin, FÃ¡bio Ricardo (REVISTA DE AGRICULTURA, 2021)
The objective of this study was to evaluate the technical and economic feasibility of installing central pivot irrigation systems in current days (Scenario A) and in two future scenarios, one with a 10% increase in rainfall (Scenario B1) and the other with 10% reduction in rainfall (Scenario B2). For both future scenarios, an increase of 2ÂºC in the global temperature and the concentration of atmospheric carbon dioxide (CO2) increasing to 528 ppm (parts per million) were considered. For the study, the recommendation for an area of clayey soil and with the sugarcane cycle was evaluated on three different planting dates: May 15, August 15 and November 15. The DSSAT/CANEGRO model was used, and under the current conditions, the simulations indicated greater yield for planting in May, both for rainfed and irrigated. For scenario B1, there was an increase in yield of 22% for rainfed and 33% for irrigated. In addition, irrigation provided yield gains in the two future scenarios of 13% and 14% for B1 and B2, respectively. Based on the results obtained, central pivot irrigation proved economically viable in the simulated climatic conditions. Therefore, the increase in sugarcane production provided by irrigation in agronomic management was sufficient to make investment in the region in question feasible. It is suggested to repeat the study in other regions, since the existing synergy between the factors that define agricultural yield can change the decision making about the implantation of irrigation systems in the production environment.